Mengungkap Potensi Kluwak (Pangium edule Reinw) Sebagai Antioksidan Alami dan Penghambat Senescence - Ratih Kurnia Wardani; Yurananda Magnalia Putri; Dhella Angelina Nurjanah; Ratna Asmah Susidarti (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Senescence is a condition that causes tissue dysfunction, causing problems such as premature senescence. Premature senescence is caused by oxidative stress that comes from reactions in the body and the environment (UV rays, X rays, and free radicals). Kluwak seeds (Pangium edule Reinw) contain a variety of powerful antioxidant compounds such as vitamin E, vitamin C, polyphenols, flavonoids (quercetin and catechins), quinine, and β carotene. This narrative review aims to uncover kluwak’s potential as a natural senescence-inhibiting agent for antioxidants. The literature search method with the Booelan technique is used by combining several keywords with the notation AND, OR, NOT from various literatures from national and international journals published from various databases. The results showed that the compounds in kluwak can prevent oxidative stress that causes senescence because they have antioxidant activity from phenolic groups and conjugated double bonds. The mechanisms possessed by kluwak seeds are: stabilizing ROS, increasing antioxidant enzymes in the body, inhibiting prooxidant enzymes, preventing lipid peroxidation, and inhibit markers of senescence (anti-SASP). Therefore, kluwak is used as an anti-senescence agent in the form of cosmetic preparations that have local effects, such as hydrogels which are easy and safe to use in the body.